Assessment of phyllochron and tillers contribution to grain yield of rice - Nandhakumar, M R; Velayudham, K; Thavaprakaash, N; Govindan, R (ORYZA-An International Journal of Rice, 2018)
Field experiments were carried out at Tamil Nadu Agricultural University, Coimbatore, India during samba (August-December) season of 2012 and 2013 to address the contribution of phyllochron and main culm, primary, secondary and tertiary panicles to grain yield of low land rice with the objective of to investigate the tillering and grain production in main culm, primary, secondary and tertiary tillers due to varied crop geometry, age and number of seedlings in rice. The experiment consisted of three main-plot treatments and replicated thrice in a split plot design. Crop geometry of 25 x 25 cm in association with 14 DOS with one seedling hill-1 resulted higher panicle weight (5.35, 4.16, 3.55 and 2.90 g) on main culm, primary, secondary and tertiary panicles, respectively compared to all other combinations. Combination of transplanting of rice at wider spacing of 25 x 25 cm and 14 DOS with one seedling hill-1 was found to record higher grain yield (7303 kg ha-1) than other treatments.